1993
DOI: 10.1128/jb.175.1.128-132.1993
|View full text |Cite
|
Sign up to set email alerts
|

Oxygen-dependent transcriptional regulation of cytochrome aa3 in Bradyrhizobium japonicum

Abstract: Cytochrome aa3 is one of two terminal oxidases expressed in free-living Bradyrhizobium japonicum but not symbiotically in bacteroids. Difference spectra (dithionite reduced minus ferricyanide oxidized) for membranes from cells incubated with progressively lower 02 concentrations showed a concomitant decrease in theA603, the absorption peak characteristic of cytochrome aa3. The level of N,N,N',N'-tetramethyl-p-phenylenediamine oxidase activity, a measure of cytochrome aa3 activity, was also found to depend on t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
19
0

Year Published

1996
1996
2015
2015

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(19 citation statements)
references
References 33 publications
0
19
0
Order By: Relevance
“…A K m of 56 nM was determined for such an alternative oxidase (or oxidase mixture). This value is about eightfold higher than that of the cbb 3 -type oxidase and falls within (5,14), the values of 55 to 62 nM measured with aerobically grown coxA ϩ strains probably reflect its K m for O 2 , even more so as the V max for the coxA mutant drops by almost 80% compared with that for the wild type (Table 2). In this context it should be noted that the derived K m for O 2 of the aerobically expressed B. japonicum oxidases accords well with the recently reported K m values of the low-affinity cytochrome boЈ from E. coli (46 nM) (11) and the mitochondrial cytochrome aa 3 from soybean (50 to 147 nM) (26,27).…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…A K m of 56 nM was determined for such an alternative oxidase (or oxidase mixture). This value is about eightfold higher than that of the cbb 3 -type oxidase and falls within (5,14), the values of 55 to 62 nM measured with aerobically grown coxA ϩ strains probably reflect its K m for O 2 , even more so as the V max for the coxA mutant drops by almost 80% compared with that for the wild type (Table 2). In this context it should be noted that the derived K m for O 2 of the aerobically expressed B. japonicum oxidases accords well with the recently reported K m values of the low-affinity cytochrome boЈ from E. coli (46 nM) (11) and the mitochondrial cytochrome aa 3 from soybean (50 to 147 nM) (26,27).…”
Section: Discussionmentioning
confidence: 96%
“…In such mutants, we consistently measured 20% residual oxidase activity with bacteroids or with cells grown microaerobically or anaerobically (30), but we do not know the relative contribution of each of the three alternative oxidases to this activity. It has been suggested that the level of cytochrome aa 3 is down-regulated in symbiosis (14,23), and the physiological conditions for maximal expression of the CoxMNOP oxidase and the CoxX oxidase ( Fig. 1) are not known at all.…”
Section: Discussionmentioning
confidence: 99%
“…However, it was unexpected that the quadruple mutant strain QXAa was unable to grow aerobically (Fig. 1A), because aa 3 -type oxidases play major roles in aerobic growth in many bacterial species (23)(24)(25)(26). Transcription of the cox genes encoding aa 3 is repressed by the two-component regulator RoxSR and is dependent on the stationary-phase sigma factor RpoS (21).…”
Section: Figmentioning
confidence: 99%
“…aa 3 is closely related to mitochondrial terminal oxidases. aa 3 -type oxidases typically have low affinity for oxygen and function as main enzymes under high-oxygen conditions in many bacterial species (23)(24)(25)(26). However, in P. aeruginosa, aa 3 is expressed at very low levels in nutrient-rich medium under high-oxygen conditions and is upregulated only in response to nutrient starvation (21).…”
mentioning
confidence: 99%
“…Cytochrome aa 3 is a terminal oxidase necessary for normal aerobic respiration; its expression is diminished or absent in microaerobically cultured cells and in symbiotic bacteroids, and the message level of a gene encoding a subunit of the oxidase is under O 2 control (17). The persistence of cytochrome aa 3 in O 2 -restricted cells of mutant strain 7360 (Fig.…”
Section: Discussionmentioning
confidence: 99%